REGULASI AI DALAM PASAR MODAL DIGITAL: TANTANGAN HUKUM TERHADAP ALGORITMA TRADING OTOMATIS, MANIPULASI PASAR, DAN PERLINDUNGAN INVESTOR RITEL - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
The artificial intelligence (AI) revolution has fundamentally transformed the digital capital markets, shifting trading mechanisms from human interaction towards an ecosystem dominated by high-speed automated trading algorithms. However, the integration of this technology presents complex legal challenges that have not yet been accommodated by conventional regulatory frameworks, particularly regarding the accountability of autonomous systems, the detection of algorithmic market manipulation, and the protection of retail investors from structural information asymmetry. This study employs a literature review method with a legal-normative approach to analyse regulatory gaps concerning AI in the Indonesian capital market. The findings reveal that existing provisions in Law No. 8 of 1995 on the Capital Market and OJK regulations are generic; they do not define technical parameters of AI-based manipulation such as spoofing, layering, and quote stuffing, and they obscure the attribution of legal liability in the event of systemic incidents caused by autonomous algorithms. Retail investors, who account for 85 per cent of all investors in the Indonesian capital market, face serious vulnerabilities due to temporal asymmetry, the exploitation of cognitive biases through dark patterns, and the absence of mandatory Explainable AI (XAI) mechanisms. This study recommends the adoption of a risk-based regulation approach that classifies AI systems according to risk level, obligations regarding algorithmic transparency and periodic independent audits, strengthening of supervisory capacity based on Regulatory Technology (RegTech), and cross-jurisdictional regulatory harmonisation to address cross-border manipulation. This comprehensive reform is an absolute prerequisite for establishing fair, accountable, and sustainable AI governance, ensuring that technological innovation does not compromise market integrity and the fundamental rights of retail investors within Indonesia’s digital capital market ecosystem.